MEDIATION OF CUSTOMER TRUST IN THE INFLUENCE OF ADVERTISING ON INSTAGRAM SOCIAL MEDIA AND INNOVATION OF SCARLETT WHITENING PRODUCTS ON THE REPURCHASE INTENTIONOF ONLINE SHOPPINGIN YOGYAKARTA CITY - Aulia Rachma Dinantika; Setyabudi Indartono (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This study aims to explain the mediation of customer trust in the influence of Instagram social media advertising and Scarlett Whitening product innovation on online shopping purchase intentions in Yogyakarta City. This research is a quantitative research with a survey method. The population in this study were women who had used Scarlett Whitening products more than once. The sampling technique in this study was purposive sampling with a total sample of 165 people. The data collection technique uses an online questionnaire which has been tested for validity using Confirmatory Factor Analysis and reliability using Cronbach Alpha. The data analysis technique used is multiple regression. The results of the study are as follows (1) There is a positive and significant effect of social media on purchase intention with a beta coefficient of 0.284 (p <0.001). (2) There is a positive and significant effect of product innovation on purchase intention with a beta coefficient of 0.451 (p <0.001). (3) There is a positive and significant influence of customer trust on purchase intention with a beta coefficient of 0.374 (p <0.001). (4) Customer trust mediates the effect of social media on purchase intention with a beta coefficient value of 0.284 (p <0.001) decreasing to 0.156 (p <0.05) (5) Customer trust mediates the effect of product innovation on purchase intention with a beta coefficient value the resulting 0.451 (p < 0.001) decreased to 0.355 (p < 0.05). From these results, it can be concluded that social media, product innovation, and customer trust can increase the intention to buy Scarlett Whitening products. Therefore, it is hoped that the Scarlett Whitening Company can become a reference in business management by optimizing product variations and brand utilization in the cosmetic and skin care industry.